Effect of Three Different Grip Angles on Physiological Parameters During Laboratory Handcycling Test in Able-Bodied Participants - Abel, Thomas; Burkett, Brendan; Thees, Barbara; Schneider, Stefan; Askew, Christopher D.; Strüder, Heiko K. (Frontiers in Physiology, 2015)
Introduction: Handcycling is a relatively new wheelchair sport that has gained increased popularity for people with lower limb disabilities. The aim of this study was to examine the effect of three different grip positions on physical parameters during handcycling in a laboratory setting. Methods: Twenty one able-bodied participants performed three maximum incremental handcycling tests until exhaustion, each with a different grip angle. The angle between the grip and the crank was randomly set at 90° (horizontal), 0° (vertical), or 10° (diagonal). The initial load was 20 W and increased by 20 W each 5 min. In addition, participants performed a 20 s maximum effort. Results: The relative peak functional performance (W/kg), peak heart rate (bpm), associated lactate concentrations (mmol/l) and peak oxygen uptake per kilogram body weight (ml.min−1.kg−1) for the different grip positions during the stage test were: (a) Horizontal: 1.43 ± 0.21 W/kg, 170.14 ± 12.81 bpm, 9.54 ± 1.93 mmol/l, 30.86 ± 4.57 ml/kg; (b) Vertical: 1.38 ± 0.20 W/kg, 171.81 ± 13.87 bpm, 9.91 ± 2.29 mmol/l, 29.75 ± 5.13 ml/kg; (c) Diagonal: 1.40 ± 0.22 W/kg, 169.19 ± 13.31 bpm, 9.34 ± 2.36 mmol/l, 29.39 ± 4.70 ml/kg. Statistically significant (p < 0.05) differences could only be found for lactate concentration between the vertical grip position and the other grips during submaximal handcycling. Conclusion: The orientation of three different grip angles made no difference to the peak load achieved during an incremental handcycling test and a 20 s maximum effort. At submaximal load, higher lactate concentrations were found when the vertical grip position was used, suggesting that this position may be less efficient than the alternative diagonal or horizontal grip positions.